Bioremediation of Cr (VI) by novel microalgal strain - Tripathi G.; Dubey P.; Irum P.; Ahmad S.; Mishra V.; Farooqui A. (My University, 2025)
The present study aims at the isolation of Cr (VI) tolerant microalgae from wastewater collected from local bike garages. The wastewater had a continued spillage of engine oil, petrol, grease, and chain lube waste. The isolated microalgae were first sequenced by using 18S rRNA sequencing method. The nucleotide sequence obtained was analyzed via BLAST, the isolated microalga showed maximum similarity with Scenedesmus species. The sequence was submitted to NCBI, and the microalgae was identified as Scenedesmus species GTAF1 IU accession no. OM903800. The bioremediation potential of the isolated microalgae was evaluated for the removal of Cr (VI) in synthetic wastewater. The Cr (VI) removal efficiency was estimated at 0.2, 0.4, 0.6, and 0.8 g L−1 of inoculum concentration under autotrophic and heterotrophic modes. The highest removal efficiency of 98.9% and 99.9% was obtained at 0.8 g L−1 inoculum concentration under autotrophic and heterotrophic modes of operation respectively. On increasing the metal concentration from 5 to 10 ppm, a decrease in the biomass quality and quantity was observed. This increased metal stress resulted in an enhanced carbohydrate and lipid concentration. However, the protein concentration was found to be decreased. Cr (VI) removal efficiency was highest in heterotrophic conditions. This study provides a novel insight for removing Cr (VI) and concomitantly enhancing the lipid content of isolated strains under heterotrophic conditions. Owing to enhanced lipid content, the reported curation of wastewater may also be used in harnessing the potential of isolated microalga in biofuel production. © 2024 Taylor & Francis Group, LLC.